Is the Role of Ideologists Central in Terrorist Networks? A Social Network Analysis of Indonesian Terrorist Groups - Milla, Mirra Noor; Hudiyana, Joevarian; Cahyono, Wahyu; Muluk, Hamdi (Frontiers in Psychology, 2020)
This study aims to describe how group leaders operate with their social ties of jihadi terrorists, using social network analysis. Data was collected through documents and interviews from terrorist detainees who were involved in jihadi terrorism activities in Indonesia. We found that relational trust with operational leaders plays an important role in terrorist social networks. More specifically, operational leaders possess a higher degree of centrality and betweenness centrality compared to ideological leaders, as operational leaders happened to possess stronger social ties (with close friends or respected authorities). Furthermore, we also found that terrorist networks in Indonesia consist of a large group of cells with low density, where members are not strongly connected to each other. The only bridges that were strong in these social networks were those involving operational leaders. This study confirmed previous studies that terrorist groups operate in a cell system, but lead to a novel finding that ideological leaders may play a limited or indirect influence in operational networks.